Who understands comics? questioning the universality of visual language comprehension - Cohn, Neil (Bloomsbury Academic, 2021)
Nominated for the 2021 Eisner Award for Best Academic/Scholarly Work••Drawings and sequential images are so pervasive in contemporary society that we may take their understanding for granted. But how transparent are they really, and how universally are they understood? Combining recent advances from linguistics, cognitive science, and clinical psychology, this book argues that visual narratives involve greater complexity and require a lot more decoding than widely thought. Although increasingly used beyond the sphere of entertainment as materials in humanitarian, educational, and experimental contexts, Neil Cohn demonstrates that their universal comprehension cannot be assumed. Instead, understanding a visual language requires a fluency that is contingent on exposure and practice with a graphic system. Bringing together a rich but scattered literature on how people comprehend, and learn to comprehend, a sequence of images, this book coalesces research from a diverse range of fields into a broader interdisciplinary view of visual narrative to ask: Who Understands Comics?